Predicting mire distribution using species distribution models (SDMs) and GISc : a case study of the Prince Edward Islands (PEIs) - Hansen, Christel (University of Pretoria, 2022)
Dissertation (MSc (Geoinformatics))--University of Pretoria, 2022.